Antioxidants and α-glucosidase inhibitory activities from peels of Salak (Salacca zalacca) fruit - Saleh, Mohammed S M; Siddiqui, Mohammad Jamshed Ahmad; Rahman, Md. Mokhlesur; Mat So'ad, Siti Zaiton (2017)
Introduction: Salacca zalacca or salak is a species of palm tree which belongs to Arecaceae family and native to Indonesia and Malaysia. Normally salak grows in clusters and produces an edible fruit also known as snake fruit due to the reddish brown scaly skin. Although traditionally used as an antidiabetic, it needs scientific validation for this indication. Design and Methodology: The aims of this study is to evaluate the antioxidant and α-glucosidase inhibitory activities of different extracts of peels of Salak fruit. The extracts were prepared successively through maceration process at room temperature with different percentile of ethanol: water (100% ethanol to 0% ethanol). Preliminary phytochemical screenings conducted on different extracts followed by the estimation of total phenolic and flavonoids contents. Free radical scavenging activity was determined using DPPH as well as α-glucosidase inhibitory activity was performed using α-glucosidase enzyme. Findings and Results: Phytochemical screening shows the presence of phenolic and flavonoids in all the extracts. 100% ethanol extract shows the highest phenolic content 116.70 µg/ml while 60% ethanol extract has the lowest content 18.65 µg/ml using gallic acid as reference. Total flavonoids contents were observed moderately low in all extracts. 100% ethanol extract was observed to exhibit highest radical scavenging and α-glucosidase inhibitory activities IC50 49.210 µg/ml and IC50 11.629µg/ml respectively. Water extracts have the lowest radical scavenging activity as well as α-glucosidase activity. The higher phenolic contents in ethanol extracts may be attributed to the high phenolic compounds present in the extracts. The high antioxidant and α-glucosidase inhibitory properties of S. zalacca indicated that the fruit possessed potential health benefits properties. Contribution and originality: The economic and pharmaceutical values are anticipated to increase its incredible contribution to the Malaysian population.